PENGARUH FAMILY CONTROL, FIRM SIZE, FIRM RISK, DAN FIRM LIFE CYCLE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Servin Servin (Business Accounting Review, 2014)
This study aims to examine the effect of family control, firm size, firm risk, and firm lifecycle towards profitability and firm’s value. Sampels were taken from 27 consumer goodscompanies, listed in Indonesia Stock Exchange, ranging from 2010 – 2012. The hypotheseswere tested using multiple regression analysis. In this study, profitability was measured byROA (Return on Asset) and firm’s value was measured by Tobin’s q. The result were, familycontrol and life cycle stage-growth had negative influence towards profitability and firm’svalue while firm size and life cycle stage-mature had positive influence. Firm risk had noinfluence to both of profitability and firm’s value.